Association between complete blood cell count-derived inflammatory biomarkers and gallstones prevalence in American adults under 60 years of age - Fu, Chang; Chen, Junhong; Wang, Yongxin; Yang, Yibo; Li, Xiaocong; Liu, Kai (Frontiers in Immunology, 2025)
BackgroundThe trend of gallstones occurring in younger populations has become a noteworthy public health issue. This study aims to investigate the association between complete blood cell count (CBC)-derived inflammatory indicators and gallstones in adults under 60 years of age in the United States.MethodsThis cross-sectional study used data from the National Health and Nutrition Examination Survey (NHANES) from 2017 to 2020. Associations between CBC-derived inflammatory biomarkers and gallstones were assessed using multivariable logistic regression models, with results presented as odds ratio (OR) and 95% confidence interval (CI). Restricted cubic splines (RCS) were employed to examine potential non-linear relationships. Subgroup analyses were also conducted to explore differences across population subgroups.ResultsThis study comprised 4,977 participants, among whom 398 were diagnosed with gallstones. After adjusting for confounding variables, the highest quartile of systemic inflammation response index (SIRI) [OR (95%CI): 1.65(1.12,2.43)], systemic immune-inflammation index (SII) [OR (95%CI): 1.53(1.05,2.25)], monocyte-to-lymphocyte ratio (MLR) [OR (95%CI): 1.66(1.16,2.37)], and pan immune inflammatory value (PIV) [OR (95%CI): 1.82(1.23,2.71)] were associated with a significantly increased risk of gallstones compared to the lowest quartiles. RCS plots indicated a nonlinear relationship between several inflammatory biomarkers and gallstones.ConclusionOur study found that SIRI, SII, MLR, and PIV can serve as clinical indicators for predicting the risk of gallstones in adults under 60 years of age in the United States.